Fisheries for Food and Nutritional Security - Moza, Usha (Indian Farming, 2015)
In an underdeveloped country like India with more than 1.2 billion population, having least access to nutritional diet, fishery provide an essential contribution to food and nutritional security in the interior parts of India and to low income group of people directly and indirectly providing means of livelihood through Aquaculture.